Health externalities and policy: The role of social preferences - Laura Alfaro; Ester Faia; Nora Lamersdorf; Farzad Saidi (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2021)
Social preferences facilitate the internalization of health externalities, for example by reducing mobility during a pandemic. We test this hypothesis using mobility data from 258 cities worldwide alongside experimentally validated measures of social preferences. Controlling for time-varying heterogeneity that could arise at the level at which mitigation policies are implemented, we find that they matter less in regions that are more altruistic, patient, or exhibit less negative reciprocity. In those regions, mobility falls ahead of lockdowns, and remains low after the lifting thereof. Our results elucidate the importance, independent of the cultural context, of social preferences in fostering cooperative behavior.
Keywords: D01; D62; D64; D91; I10; I18; 330; social preferences; pandemics; mobility; health externalities; mitigation policies